Dinamika Extraordinary Measures: Pengaruh Narcoterrorist terhadap Kekuasaan Pemerintah dalam Mengendalikan Keamanan Ekuador 2024: Extraordinary Measures Dynamics: The Influence of Narcoterrorism on Government Power in Controlling Ecuadorian Security 2024 - Muharram, Royabfihi Adam; Wongso, Jennifer Meiliana; Natania, Nadine Hannah (Jurnal Sentris, 2025)
ABSTRACT The escalating actions of narcoterrorist groups have triggered a security crisis in Ecuador. As the highest authority, the government has employed all possible measures to curb the influence of narcoterrorist groups and restore stability. These efforts have been carried out through extraordinary measures as a form of securitization, including military operations aimed at addressing existential threats. However, despite the implementation of such extraordinary measures, the security crisis remains unresolved and persists as a tangible reality. This situation places Ecuador in a position where the dominance of narcoterrorist groups significantly affects the country's dynamics. Based on this phenomenon, this study examines how extraordinary measures in Ecuador have influenced the state’s power dynamics and the narcoterrorist groups' control over security in 2024. The research adopts a qualitative approach, utilizing secondary data such as literature, official websites, and reports. The analysis is grounded in securitization theory, focusing on how the state employs extraordinary measures to confront existential threats. The study aims to provide an understanding of the interaction dynamics between the government and narcoterrorist groups and how securitization is implemented to stabilize Ecuador's security conditions. The findings reveal that the government employs extraordinary measures as a tool of securitization to reclaim its authority from the influence and dominance of narcoterrorist groups. Keywords: Ecuador, Securitization, Extraordinary Measures, Government Authority, Narcoterrorist.